2003
DOI: 10.1034/j.1600-051x.2003.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of erosion and abrasion on enamel and dentine: a model in situ using toothpastes of different abrasivity

Abstract: Erosion increases the susceptibility of enamel to toothpaste abrasion. Dentine is considerably more susceptible than enamel to erosion and abrasion alone or combined. Dentine loss appears to correlate with toothpaste abrasivity (RDA value).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
151
5
25

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(190 citation statements)
references
References 23 publications
9
151
5
25
Order By: Relevance
“…The observation that abrasion of eroded dentin increased along with the RDA-value confirms the results of Hooper et al 9 who showed that a toothpaste with higher RDA (RDA 189) also caused higher wear on eroded dentin than a less abrasive toothpaste (RDA 85).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The observation that abrasion of eroded dentin increased along with the RDA-value confirms the results of Hooper et al 9 who showed that a toothpaste with higher RDA (RDA 189) also caused higher wear on eroded dentin than a less abrasive toothpaste (RDA 85).…”
Section: Discussionsupporting
confidence: 79%
“…This has been shown for sound dental hard tissues [6][7][8] and, in a few studies, also for eroded enamel and dentin. 9,10 Toothbrush abrasivity is analysed by a radiotracer method, which determines relative abrasivity of sound enamel and dentine (REA and RDA, respectively) compared to reference abrasives.…”
Section: Introductionmentioning
confidence: 99%
“…The Relative Dentin Abrasion (RDA) and Relative Enamel Abrasion of a toothpaste define its abrasive potential on a normalised scale with an accepted standard material serving as a reference [111]. In situ studies to investigate the effects of abrasion on dentin have shown that dentin is considerably more susceptible than enamel to abrasion alone [112] and that significant differences in dentin wear can be detected between a moderate- and high-RDA toothpaste [113]. These effects on enamel can be explained by the fact that most toothpaste contains abrasives which are softer than enamel.…”
Section: Lesion Localisationmentioning
confidence: 99%
“…Therefore, reliable detection of minimal losses below 1 tJm are generally difficult to accomplish with profilometry, although Hooper et al [53] [38] have demonstrated that profilom-etry was able to distinguish between different abrasivities of toothpastes creating hard tissue loss of about 0.5 tJm. For such precise measurements with low varia-tions, meticulous flattening and polishing of sample surface is an important step.…”
Section: Surface Profilometrymentioning
confidence: 99%